Parkinson's Disease in Relation to Pesticide Exposure and Nuclear Encoded Mitochondrial Complex I Gene Variants. (12th June 2006) - Corder, Elizabeth H.; Mellick, George D.
Abstract : Parkinson's disease (PD) is a common age-related neurodegenerative disorder thought to result from the integrated effects of genetic background and exposure to neuronal toxins. Certain individual nuclear-encoded mitochondrial complex I gene polymorphisms were found to be associated with∼ 2 -fold risk variation in an Australian case-control sample. We further characterized this sample of306 cases and321 controls to determine the mutual information contained in the22 SNPs and, additionally, level of pesticide exposure: five distinct risk sets were identified using grade-of-membership analysis. Of these, one was robust to pesticide exposure (I), three were vulnerable (II, III, IV), and another (V) denoted low risk for unexposed persons. Risk for individual subjects varied> 16 -fold according to level of membership in the vulnerable groups. We conclude that inherited variation in mitochondrial complex I genes and pesticide exposure together modulate risk for PD.